Membrane technology in water and wastewater treatment - Hillis, P. (Royal Society of Chemistry, 2000)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. Presenting a useful reference to the current state of membrane technology and its likely future growth, this book covers all aspects of the technology and its applications in the water industry. Drawing on the experience of international experts, Membrane Technology in Water and Wastewater Treatment encompasses many practical applications of specific membranes, including MF, UF, NF, RO and EDR, in the treatment of ground and surface water, backwash water, seawater, and industrial and domestic wastewater. Novel applications, process enhancements and the latest systems are also discussed. This book is an excellent guide to membrane technology and will be of great interest to water companies, industrialists, legislative bodies and anyone with an interest in the technology or its applications.
Proceedings of the International Conference on Membrane Technology in Water and Wastewater Treatment, held at Lancaster University from March 27-29, 2000, organized by the Royal Society of Chemistry Water Chemistry Forum, the European Desalination Society, and the SCI Separation Science and Technology Group.
Keywords: Membrane separation -- Congresses.; Water -- Purification -- Congresses.; Sewage -- Purification -- Congresses.; Membranes (Technology) -- Congresses.; Water quality management -- Congresses.; elektronické knihy; electronic books